The Effect of Basal Melting of the Shirase Glacier Tongue on the CO2 System in Lützow‐Holm Bay, East Antarctica. Issue 5 (25th May 2021) - Kiuchi, Masaaki; Nomura, Daiki; Hirano, Daisuke; Tamura, Takeshi; Hashida, Gen; Ushio, Shuki; Simizu, Daisuke; Ono, Kazuya; Aoki, Shigeru
Abstract: To clarify the effect of basal melting of ice tongues/ice shelf on the CO2 system in the Antarctic continental margin, seawater samples were collected for analysis of dissolved inorganic carbon (DIC), total alkalinity (TA), nutrients, chlorophyll a (chl.a), and oxygen isotopic ratios at the ice front of the Shirase Glacier Tongue (SGT) in Lützow‐Holm Bay (LHB), East Antarctica during the summers of 2017 and 2018. At depths greater than ∼20 dbar in LHB, CO2 system parameters were strongly influenced by the dilution effect of SGT basal melting and the inflow of modified Circumpolar Deep Water (mCDW). The distributions of DIC and TA agreed well with an offshore origin of mCDW that flowed beneath the SGT and mixing of basal meltwater and mCDW beneath the SGT. The fraction of SGT meltwater was highest at the station near the ice front. Dilution by SGT basal meltwater reduced the partial pressure of CO2 in the mCDW from 431 to 387 μatm. The water then became a sink rather than source of atmospheric CO2 . In the sea surface, DIC and TA were strongly influenced by biological processes. Salinity‐normalized DIC decreased with the increase of salinity‐normalized TA in accord with 106:16 C:N molar stoichiometry; the chl.a concentration at the sea surface was as high as 31 μg L −1 . Plain Language Summary: Oceanographic observations were made during the summers of 2017 and 2018 near the ice shelf in an ice‐covered bay in East Antarctica. Results revealed that the parameters such as dissolved inorganic carbon (DIC), total alkalinity (TA), and nutrients at subsurface layer (>20 m) was strongly influenced by the dilution effect of the melting of ice sheet and the inflow of warm and high salinity water from outside of the bay. In contrast, within the surface layer, DIC, TA, and nutrients were strongly influenced by phytoplankton activity. Key Points: The CO2 system is strongly influenced by the dilution effect of the basal melting of the Shirase Glacier Tongue (SGT) The decrease of pCO2 by basal melting caused the water to shift from a CO2 source to a sink of atmospheric CO2 in Lützow‐Holm Bay Surface water was strongly influenced by biological processes near the SGT